Living and Learning with Chronic Disease: Toward Better Methods of Education - Lisa M. Baumgartner; Katharine Preissner (Adult Education Research Conference, 2015)
Learning to live with a chronic disease is a lifelong endeavor. Literature concerning learning, identity, and education as it relates to chronic illness are reviewed. Session participants will discuss best practices regarding learning and health education for the chronically ill.
Keywords: chronic disease; learning; education; identity